Local enhancement of hydrogen production by the hydrolysis of Mg17Al12 with Mg “model” material - Al Bacha, S. (2022)
The effect of galvanic coupling on the corrosion behavior of Mg and Mg17Al12 in Mg-Al alloys was studied by Scanning ElectroChemical Microscopy (SECM). The effect of galvanic coupling between Mg and Mg17Al12 was investigated using a “model” Mg+Mg17Al12 material with a controlled microstructure to evaluate the hydrogen evolution at a micrometric scale. SECM maps revealed that galvanic coupling between Mg and Mg17Al12 accelerates the corrosion rate (formation of a thicker passive layer) of both components. Mg17Al12 acts controversially to a conventional cathode in galvanic system since hydrogen production by its hydrolysis reaction was found to increase due to the electron transfer with the anode (Mg).